The influence of the utilization, use, trust, and ability of information system user technique Accounting for employee performance On the people's credit banks in Badung regency - Selvia Dewi, Ni Kadek Indah; Yadnyana, I Ketut (E-Jurnal Akuntansi, 2018)
The development of technology from the influence of globalization is now so fast, one of which is used for the progress of the company. Companies need an accounting information system that is useful for long-term life of the company where the technology can improve employee performance that will provide convenience to the company in achieving its goals. The purpose of this study is to determine the effect of interest in the use, use, trust, and ability of user information systems accounting techniques on employee performance. The population in this study are employees who use the accounting information system contained in Rural Banks in Badung regency. Where is the BPR in Badung regency numbered 52 BPR. The sample used in this study is as many as 100 respondents The number of samples obtained by using slovin formula. Data analysis used in this research is multiple regression analysis. This study found that interest in utilization, use, trust, and technical ability of user accounting information system have a positive effect on employee performance. This shows the four variables are able to improve employee performance.